Cutting the Gordian knot: a historical and taxonomic revision of the Jurassic crocodylomorph Metriorhynchus. Issue 2 (3rd November 2020) - Young, Mark T; Brignon, Arnaud; Sachs, Sven; Hornung, Jahn J; Foffa, Davide; Kitson, James J N; Johnson, Michela M; Steel, Lorna
Abstract: Metriorhynchidae was a clade of extinct crocodylomorphs that adapted to a pelagic lifestyle, becoming a key component of Mesozoic lagoonal and coastal marine ecosystems. The type genus Metriorhynchus is one of the best-known genera of Mesozoic crocodylomorphs, and since the mid-19 th century, the 'concept' of Metriorhynchus has become associated with the referred species Me. superciliosus . Historically Metriorhynchus has been the most species-rich genus in Metriorhynchidae, with most Middle Jurassic species and many Late Jurassic species referred to the genus at some point in their history. However, the type species Me. geoffroyii has largely been omitted in the literature. Its type series is a chimera of multiple metriorhynchid species, and a type specimen has never been designated. Moreover, phylogenetic analyses have repeatedly shown that the 19 th –20 th century concept of Metriorhynchus is not monophyletic – to the point where only referring every metriorhynchid species, and some basal metriorhynchoids, to the genus would render it monophyletic. Herein we designate a lectotype for Me. geoffroyii, re-describe it and restrict the genus Metriorhynchus to the type species. We also establish the new genus Thalattosuchus for Me. superciliosus, thereby cutting the 'Gordian knot' of Metriorhynchus with Th . superciliosus .